Jesus, Prosperity Gospel, and Poverty in Africa - Oladimeji, Elijah (Yorkshire Publishing, 2020)
Poverty is a big problem in Africa, particularly black Africa. Basic necessities such as food, water, and shelter remain out of reach of many. According to some statistics, nearly 50% of all Africans live below or on the edge of poverty, earning only around $1.25 per day. Access to health care, education and shelter remains a gigantic problem.